2004
DOI: 10.1002/pssc.200304279
|View full text |Cite
|
Sign up to set email alerts
|

Surface processing of CdTe crystals by an excimer laser and its application in fabricating nuclear radiation detectors

Abstract: PACS 85.40.Ry Excimer laser based surface processing of CdTe crystals is investigated in two different ways, namely laser ablation and laser enhanced impurity doping, for their applications in fabrication of nuclear radiation detectors. Micro-pattering on CdTe surface is performed by irradiating the laser through a shadow mask placed on the CdTe in a high vacuum condition. On the other hand, single pulse laser irradiation on the thin In-layer evaporated CdTe surface at a high-pressure argon gas environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…1 It has been reported that laser processes for CdTe such as crystal growth and impurity doping were performed. [5][6][7][8] Low energy density laser irradiation was used in these laser processes. 7,8 This suggests that KrF excimer laser irradiation enables highspeed etching of CdTe.…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been reported that laser processes for CdTe such as crystal growth and impurity doping were performed. [5][6][7][8] Low energy density laser irradiation was used in these laser processes. 7,8 This suggests that KrF excimer laser irradiation enables highspeed etching of CdTe.…”
Section: Introductionmentioning
confidence: 99%